Magnetic Nanoparticle-Based High-Performance Positive and Negative Magnetic Resonance Imaging Contrast Agents - Tirusew Tegafaw; Shuwen Liu; Mohammad Yaseen Ahmad; Abdullah Khamis Ali Al Saidi; Dejun Zhao; Ying Liu; Sung-Wook Nam; Yongmin Chang; Gang Ho Lee (MDPI AG, 2023)
In recent decades, magnetic nanoparticles (MNPs) have attracted considerable research interest as versatile substances for various biomedical applications, particularly as contrast agents in magnetic resonance imaging (MRI). Depending on their composition and particle size, most MNPs are either paramagnetic or superparamagnetic. The unique, advanced magnetic properties of MNPs, such as appreciable paramagnetic or strong superparamagnetic moments at room temperature, along with their large surface area, easy surface functionalization, and the ability to offer stronger contrast enhancements in MRI, make them superior to molecular MRI contrast agents. As a result, MNPs are promising candidates for various diagnostic and therapeutic applications. They can function as either positive (T1) or negative (T2) MRI contrast agents, producing brighter or darker MR images, respectively. In addition, they can function as dual-modal T1 and T2 MRI contrast agents, producing either brighter or darker MR images, depending on the operational mode. It is essential that the MNPs are grafted with hydrophilic and biocompatible ligands to maintain their nontoxicity and colloidal stability in aqueous media. The colloidal stability of MNPs is critical in order to achieve a high-performance MRI function. Most of the MNP-based MRI contrast agents reported in the literature are still in the developmental stage. With continuous progress being made in the detailed scientific research on them, their use in clinical settings may be realized in the future. In this study, we present an overview of the recent developments in the various types of MNP-based MRI contrast agents and their in vivo applications.